2020
DOI: 10.1007/s13312-020-1994-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Characteristics of COVID-19 in Indian Children in the Initial Phase of the Pandemic

Abstract: Objective To assess the epidemiological and clinical characteristics of pediatric inpatients with COVID-19, early in the pandemic. Methods Clinical and laboratory profile and outcomes were studied for children (aged 1 month — 18 years) presenting between 1 April, 2020 and 20 May, 2020 with positive nasopharyngeal swab for SARS-CoV-2 by RT-PCR. Results 50 children (56% male) with median (IQR) age of 6 (2–12) years were included. Majority (56%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…Another observation was that the median (IQR) time for RT-PCR to become negative in the present cohort was 16 (12)(13)(14)(15)(16)(17)(18)(19) d, a finding similar to the report from Delhi on adult patients [24]. Studies on virological assessment of hospitalized patients with COVID-19 showed persistence of SARS-CoV-2 RNA in nasopharyngeal samples for a duration of about 2 wk [25,26].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Another observation was that the median (IQR) time for RT-PCR to become negative in the present cohort was 16 (12)(13)(14)(15)(16)(17)(18)(19) d, a finding similar to the report from Delhi on adult patients [24]. Studies on virological assessment of hospitalized patients with COVID-19 showed persistence of SARS-CoV-2 RNA in nasopharyngeal samples for a duration of about 2 wk [25,26].…”
Section: Discussionsupporting
confidence: 88%
“…Gastrointestinal symptoms were the next common manifestations. Observational studies across the world have reported similar frequency of symptoms [13][14][15][16]. A systematic review of 27 studies showed fever to be present in half (41%-58%) followed by cough (39%-51%) and rapid breathing (6%-17%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, all children were from lower socioeconomic class, all had positive close family member at home that was COVID-19 positive. A similar pattern was seen in other studies [ 6 , 7 ]. All children were from a containment zone and all had exposure to a positive household contact.…”
Section: Discussionsupporting
confidence: 91%